Análisis energético y exergético de un ciclo rankine para la producción de energía eléctrica usando la cascarilla de arroz como combustible (2021)
In the present work the energetic and exergetic analysis of a Rankine cycle for the production of electrical energy is carried out using the rice husk on a dry basis as fuel, it starts from the physicochemical characterization of the biomass with the objective of knowing the properties For energy use, obtaining a calorific value of 14.42 MJ / kg, a theoretical analysis of combustion is developed to quantify the heat generated. Starting from a conventional Rankine cycle, design parameters are established, through a thermodynamic analysis carried out with the help of the CoolProp library, from Microsoft Excel, in search of improving the use of energy through the implementation of equipment and configurations, in order to meet the requirements of the Diana Corporación / Vía Morichal plant.